Dosimetric Comparison Between Helical Tomotherapy and Volumetric Modulated Arc Therapy in Patients With Malignant Pleural Mesothelioma. Issue 3 (March 2022) - Müdder, T.; Sarria, G.R.; Henkenberens, C.; Holz, J.; Garbe, S.; Röhner, F.; Stumpf, S.; Buchstab, T.; Giordano, F.A.; Leitzen, C.
Abstract: Aims: To carry out a dosimetric comparison and constraints feasibility proof of adjuvant radiotherapy through helical tomotherapy or volumetric modulated arc therapy (VMAT) for malignant pleural mesothelioma patients after pleurectomy/decortication. Materials and methods: Retrospective calculations were carried out on previously acquired simulations. A whole-pleura volume with 50.4 Gy in 28 fractions was prescribed, simulating a no residual tumour situation. Calculations were carried out using an anisotropic analytical algorithm with a 2.0 mm grid. Beam-on time, planning target volume (PTV) coverage, homogeneity index and organ at risk exposure were compared. Results: Sixteen patient plans were calculated per device. Constraints were met overall by both modalities. For helical tomotherapy and VMAT plans, median beam-on times were 13.8 (11.6–16.1) min and 6.4 (6.1–7.0) min; P = 0.006. The median left-sided radiotherapy PTV D98 were 48.1 (48.0–48.8) Gy and 47.6 (46.5–48.3) Gy; P = 0.023. No significant difference for right-sided radiotherapy was found. PTV D2 for left-sided radiotherapy was higher with VMAT ( P = 0.014). For right-sided radiotherapy, helical tomotherapy showed higher doses ( P = 0.039). No homogeneity index differences for left-sided radiotherapy ( P = 1.00) and right-sided radiotherapy ( P = 0.598) were seen. Significant organ at risk exposure differences were found on left-sided radiotherapy whole-lung V20, as well as D50 (both P = 0.008). Higher contralateral lung and ipsilateral kidney exposures were found with VMAT plans for both treatment sides. Conclusion: Adjuvant radiotherapy after pleurectomy/decortication in malignant pleural mesothelioma patients, with a VMAT- or helical tomotherapy-based platform, is dosimetrically feasible. Lung sparing was mostly improved with helical tomotherapy. Technique selection must be carried out according to availability and clinical criteria. Highlights: To compare helical tomotherapy and VMAT plans for adjuvant pleural mesothelioma radiotherapy. Beam-on times are greatly shortened with VMAT. Target coverage is equivalent with both modalities. Overall organ at risk sparing could be slightly improved under helical tomotherapy delivery.